2022
DOI: 10.1021/acssuschemeng.2c03116
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic Generation of Cathodic Luminol Electrochemiluminescence with Carbonized Polydopamine Nanotubes at a Low Positive Potential

Abstract: The generation of luminol electrochemiluminescence (ECL) is easily disrupted by the unexpected reactive oxygen species (ROS) involved in the complicated reaction processes. Herein, we describe the preparation of carbonized polydopamine nanotubes (C-DPANTs) and their usefulness in the development of a new ECL biosensor with a high anti-interference capacity. C-PDANTs with pyridinic N and graphitic N compositions were found to accelerate the electron transfer and improve onset potential, serving as electrocataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 59 publications
(86 reference statements)
0
4
0
Order By: Relevance
“…However, under neutral conditions, the reaction rate of the luminol-H 2 O 2 system is slow, and only a quite low ECL signal can be generated, which is unfavorable to the requirement of common highly sensitive ECL analysis and detection. To date, several reports have confirmed that the ECL signal of the luminol-H 2 O 2 system can be effectively amplified by catalysts, such as metal ions, 19 porphyrins and their derivatives, 20,21 metal nanoparticles and clusters, 22,23 quantum dots, 24 carbon nanomaterials, 20,22,25,26 etc. Therefore, how to make full use of the existing catalytic system and construct a more efficient catalytic mechanism is of great significance to improve the ECL efficiency of the luminol-H 2 O 2 system.…”
Section: Introductionmentioning
confidence: 99%
“…However, under neutral conditions, the reaction rate of the luminol-H 2 O 2 system is slow, and only a quite low ECL signal can be generated, which is unfavorable to the requirement of common highly sensitive ECL analysis and detection. To date, several reports have confirmed that the ECL signal of the luminol-H 2 O 2 system can be effectively amplified by catalysts, such as metal ions, 19 porphyrins and their derivatives, 20,21 metal nanoparticles and clusters, 22,23 quantum dots, 24 carbon nanomaterials, 20,22,25,26 etc. Therefore, how to make full use of the existing catalytic system and construct a more efficient catalytic mechanism is of great significance to improve the ECL efficiency of the luminol-H 2 O 2 system.…”
Section: Introductionmentioning
confidence: 99%
“…However, in recent years, several authors reported the cathodic ECL emission in various conditions, 55,59,60 such as with catalytic nanomaterials, e.g. zinc oxide nanoparticle-modified Ni-foam, 61 carbonized polydopamine nanotubes, 62 catalase-like CoO nanorods, 63 acetylene black oxide, 64 two-dimensional NiM metal–organic framework (MOF, with M = Fe, Co, and Zn). 65 By adjusting iron single atom structures, the enhancement mechanism of luminol cathodic ECL was investigated and found to involve the production of massive reactive oxygen species for the generation of luminol radicals.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, the luminol-dissolved O 2 (DO) electrochemiluminescence (ECL) system has been widely applied in sensing , and imaging, , benefiting from the good water solubility, non-toxicity, and cost-effectiveness of luminol. , The anodic ECL emission of luminol is always bright and obvious, due to the efficient reaction between the luminol anion radical produced during positive potential scanning and reactive oxygen species (ROS) at negative potential. , Compared with the anodic luminol ECL emission, the ECL emission of luminol triggered by narrow negative potentials is more competitive, thanks to the easier reaction and low biological sample damage . Unfortunately, few efforts have been devoted to luminol cathodic ECL emission despite multi-potential luminescence features in the luminol ECL system.…”
Section: Introductionmentioning
confidence: 99%